THE EFFECT OF RELEVANCE OF THE VALUE OF ACCOUNTING INFORMATION IN AUTOMOTIVE SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Hilman Maulana; Siska Wulandari (Jurnal Ekonomi, 2023)
The relevance of the value of accounting information in the automotive sector manufacturing companies listed on the Indonesia Stock Exchange is significant for various stakeholders. For investors, the value of accounting information provides valuable insights into the financial performance and stability of a company, which can help them make informed decisions about whether to invest in the company. For management, the value of accounting information helps them understand the financial health of the company and make informed strategic decisions. Additionally, the value of accounting information is important for regulators, as it helps them ensure that companies are complying with financial reporting standards and regulations. The value of accounting information in the automotive sector manufacturing companies listed on the Indonesia Stock Exchange is critical for investors, management, and regulators, as it helps them understand the financial performance and stability of the companies.